Pharmacokinetics, Safety, and Preliminary Efficacy of Oral Trifluridine/Tipiracil in Chinese Patients with Solid Tumors: A Phase 1b, Open-Label Study - Wang X; Zhou J; Li Y; Ge Y; Zhou Y; Bai C; Shen L (Dove Medical Press, 2020)
Xicheng Wang,1 Jianfeng Zhou,2 Yan Li,1 Yuping Ge,2 Yanping Zhou,2 Chunmei Bai,2 Lin Shen1 1Key Laboratory of Carcinogenesis and Translational Research (Ministry of Education), Department of Gastrointestinal Oncology, Peking University Cancer Hospital & Institute, Beijing 100142, People’s Republic of China; 2Department of Oncology, Peking Union Medical College Hospital, Beijing 100032, People’s Republic of ChinaCorrespondence: Lin ShenKey Laboratory of Carcinogenesis and Translational Research (Ministry of Education), Department of Gastrointestinal Oncology, Peking University Cancer Hospital & Institute, No. 52, Fu Cheng Road, Hai Dian District, Beijing, People’s Republic of ChinaTel +86-010-88156175Fax +86-010-88196561Email linshenpku@163.comChunmei BaiDepartment of Oncology, Peking Union Medical College Hospital, No. 41, Da Mu Cang Hutong, Xi Cheng District, Beijing, People’s Republic of ChinaTel/ Fax +86-010-69158315Email baichunmei1964@163.comPurpose: Trifluridine/tipiracil (FTD/TPI) is approved in Japan, the United States (US), and Europe for metastatic colorectal cancer (mCRC) refractory to standard therapies. This Phase 1b open-label study focused on the pharmacokinetic (PK) and toxicity profiles of FTD/TPI in Chinese patients with solid tumors.Methods: Patients with definitive histologically or cytologically confirmed advanced/metastatic solid tumors refractory to standard treatments were enrolled. FTD/TPI (35 mg/m2) was administered orally twice daily for five consecutive days, followed by a 2-day recovery. Treatment was repeated for five consecutive days, followed by a 16-day recovery. The primary objective was to assess PK characteristics of FTD, 5-trifluoromethyl-2,4 (1H,3H)-pyrimidinedione (FTY; an inactive form of FTD), and TPI, calculated from plasma concentrations. Additionally, these PK values were compared with those from similar Phase 1 studies in patients from Japan and the US, using Tukey–Kramer’s honestly significant difference (HSD) multiple comparison tests. Safety and preliminary efficacy of FTD/TPI were assessed.Results: Fifteen patients (12 males, three females) were enrolled, most with CRC (87%). Geometric mean analysis showed that maximum plasma concentration (Cmax) of FTD increased after multiple administration (from day 1 [3019.5 ng/mL] to day 12 [3693.1 ng/mL]), and the exposure (AUC0-t) increased 2.4-fold (day 1:7796.6 ng/mL•h; day 12:18,181.3 ng/mL•h). There was no meaningful change in the exposure to FTY and TPI throughout the study. HSD tests showed comparable PK for FTD, FTY, and TPI between Chinese and Japanese patients, and comparable exposure to FTD between Chinese and US patients. Eight patients (53.3%) experienced Grade 3 treatment-emergent adverse events, most frequently anemia and fatigue (13.3%, two events each). Median progression-free survival was 1.9 months.Conclusion: FTD/TPI had an acceptable safety and efficacy profile and PK characteristics were comparable between Chinese, Japanese, and US patients, suggesting that this treatment may be suitable for Chinese patients with refractory mCRC.Trial Registration: This trial was registered at clinicaltrials.gov as NCT02261532.Keywords: Chinese, colorectal cancer, pharmacokinetics, safety, trifluridine/tipiracil